Evaluation of clinical efficacy of a combined analgetic drug "Fanigan" for symptomatic treatment of patients with pain syndrome of various genesis. - V. Y. Mamchur; S. V. Nalotov; D. S. Nosivets; V. I. Palamarchuk; V. G. Guryanov; A. J. Ogol (Medičnì Perspektivi)
The authors studied the efficacy of combined drug Fanigan (paracetamol 500 mg and diclofenac sodium 50 mg) (production of "Kusum Pharm" (Ukraine) or "Kusum Heltker PVT. LTD" (India) in tablets for symptomatic treatment of patients with pain syndrome. A pronounced clinical efficiency of its application in patients with pain syndrome of various genesis in a daily dose from 2 to 3 tablets for 3 to 7 days was established. The obtained data on the clinical efficacy of the drug. Fanigan in the treatment of patients with pain syndrome of various genesis allow to recommend it for application in wide clinical practice.